A novel flux coating method for the fabrication of layers of visible-light-responsive Ta3N5 crystals on tantalum substrates1. Issue 26 (14th July 2015) - Suzuki, Sayaka; Wagata, Hajime; Komatsus, Mugi; Minegishi, Tsutomu; Domen, Kazunari; Oishi, Shuji; Teshima, Katsuya
<x xml:space="preserve">Abstract</x> Ta3N5 crystal layers were fabricated on Ta substrates by using a novel flux coating method in an NH3 flow.